The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.15181/rfds.v16i3.1124
|View full text |Cite
|
Sign up to set email alerts
|

Discussion on the Terms of Idea Managament and Idea Managament Systems

Abstract: Although idea management (IM) and idea management systems (IMS) and related topics have been researched since 1982 and IM itself is as old as the first ideas, authors in previous research specified 18 research gaps in literature about IM and one of the most important that there is no united view on the terms IM and IMS and there are no specialized researches about these terms, as well, in the literature of IM they are not board discussed. Purpose of the research is to discuss and create definitions of terms IM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…In this paper, IM is defined as a systematic, manageable process of idea generation, evaluation, and repeated idea generation and evaluation. The IMS is defined as a tool, tool kit or complex system which provides systematic, manageable process in IM (Mikelsone and Liela, 2015). The authors use 2 IMS classifications: based on involved idea sources (internal, external, mixed) and based on the application focus (active, passive).…”
Section: Jānis Frišfeldsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this paper, IM is defined as a systematic, manageable process of idea generation, evaluation, and repeated idea generation and evaluation. The IMS is defined as a tool, tool kit or complex system which provides systematic, manageable process in IM (Mikelsone and Liela, 2015). The authors use 2 IMS classifications: based on involved idea sources (internal, external, mixed) and based on the application focus (active, passive).…”
Section: Jānis Frišfeldsmentioning
confidence: 99%
“…(2) manageable process; (3) main parts of IM are idea generation, evaluation, and repeated idea generation and evaluation (if it is needed). Based on these assumptions IMS is a tool, tool kit or complex system which provides systematic, manageable process in IM (Mikelsone and Liela, 2015). Table 1 provides a detailed description of IMS, characterising all previously mentioned elements with its sub-elements.…”
Section: Idea Management System Basic Assumptionsmentioning
confidence: 99%
“…Idea management (IM) is a process of idea generation, evaluation, and continuation. Idea management system (IMS) is a tool, tool kit or complex system which provides systematic, manageable process of idea generation, evaluation and continuation [5], [6]. In this research authors concentrates on IMS research stream that research existing IMS not creation of new systems [7]- [9].…”
Section: A Definitions and Basicsmentioning
confidence: 99%
“…Organisational effectiveness (OE) is a one of the main topics in management science [1], [2], and in recent decades topicality of OE research has grown rapidly [3], [4]. Idea management (IM) as a separate research topic emerged and became very topical from 2002 focusing mainly on IM application and problems, but also about practical increase of web-based IMS application [5].…”
Section: Introductionmentioning
confidence: 99%
“…But even as these systems become more frequently applied in the organization, there is a research gap found in literature -that there is no common view on these systems. In previously conducted research (Mikelsone & Liela, 2015), the authors have developed a definition of IMS based on more than 70 literature sources. Definition developed during the research is that IMS are systematic, manageable tools, tool kits that help users to generate, evaluate and continue this process (that is, repeated idea generation and evaluation).…”
Section: Introductionmentioning
confidence: 99%